2020
DOI: 10.1007/s42452-020-2198-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of rice husk ash and nylon fiber on engineering properties of cement mortar

Abstract: Utilization of waste materials is of utmost importance in creating a sustainable future. Industrial waste as well as recycled materials are used as supplementary cementitious materials in order to preserve the environment as well as to enhance the properties of the construction material. In the reporting work, rice husk ash (RHA) and nylon fibers were added to cement mortar (a mixture of cement, sand and water) to investigate their individual, as well as combined effect on flexural and compressive strengths, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…These data were also in compliance with other studies with similar textile synthetic and recycled fibers, which showed that 0.5% of fibrous reinforcement is efficient for increasing mechanical properties. 39,64 On the other hand, addition above 1 wt% decreased the mechanical properties of cementitious composites reinforced with cellulose fibers as mentioned by Ghasaei et al 65…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…These data were also in compliance with other studies with similar textile synthetic and recycled fibers, which showed that 0.5% of fibrous reinforcement is efficient for increasing mechanical properties. 39,64 On the other hand, addition above 1 wt% decreased the mechanical properties of cementitious composites reinforced with cellulose fibers as mentioned by Ghasaei et al 65…”
Section: Resultsmentioning
confidence: 87%
“…These data were also in compliance with other studies with similar textile synthetic and recycled fibers, which showed that 0.5% of fibrous reinforcement is efficient for increasing mechanical properties. 39,64 On the other hand, addition above 1 wt% decreased the mechanical properties of cementitious composites reinforced with cellulose fibers as mentioned by Ghasaei et al 65 From Figure 7, it is observed that, in fact, samples that achieved the lowest compressive strength (FRC1, FRC2, and FRC4) had black areas in their structures, representing air voids, and agglomerated fiber points. In addition, fibers distributed in the cementitious matrix were observed, with the presence of pores.…”
Section: Mechanical Behavior Of the Cementitious Compositementioning
confidence: 79%
See 2 more Smart Citations
“…Finalmente, varios son los investigadores que han estudiado la influencia de la CCA en morteros y hormigones con cemento Portland, con resultados que demuestran mejoras en alguna de las características del objeto de estudio respecto del mortero control [79] [80][81] [82]. También se han realizado investigaciones en hormigón de alto rendimiento [83], en morteros y hormigones con fibras de nylon [84][85] y en hormigones autocompactantes [86] [87].…”
Section: Catalizador Gastado De Craqueo Catalítico (Fcc)unclassified